A proposed model for learning meanings of quranic vocabularies through al-fatihah chapter based on dual-coding theory (DCT) - AlOsman, Abdulrahman; Ismail, Zawawi (IIUM Press, 2022)
Itis a necessity for Muslim society to learn the meanings of Quranic vocabulary especially the ones in Al-Fatihahchapter. Numerous previous studies have proven Muslim society’s lack of accurate understanding regarding the meanings of Arabic vocabulary in the Qur’anic context. This research aims to present a model to learn the meanings of the vocabulary of Al-Fatihahchapter. For this purpose, the inductive-analytical approach was employed to explore the historical roots of Quranic vocabularies teaching method among previous scholars. The same approach was used to explore the views of contemporary researchers in the field towards the process of learning Qur’anic vocabulary through multimedia in an interactive way. As a result, the researchers came out with a proposed model that followed the Dual-Coding Theory (DCT) based on dual sensory processing systems; logogens (verbal) and imagens (non-verbal). The proposed model divided the process of teaching the meanings of Al-Fatihah chapter vocabularies into four stages for each lesson. The four stages are the introduction to the lesson, the learning of the content, the strengthening of the studied content and the summary. The researchers recommend that those who are interested to learn these vocabularies and specialized institutions in charge in this matter to combine their efforts to transform this proposed model into a practical model thus applying it to all the chapters of the Holy Qur’an.